(untitled) (Texas Journal of Medical Science, 2024)
The aim of the study is to improve the results of treatment of patients with multiple lower extremity fractures by optimizing complex diagnostics and minimally invasive methods of external and internal fixation. The experience of treating 220 patients with multiple fractures of the long bones of the lower extremities in the clinic of the Republican Scientific and Practical Center of Traumatology and Orthopedics from 2016 to 2022 is presented.